If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + 6x = 23 + 7x Solving 21 + 6x = 23 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 21 + 6x + -7x = 23 + 7x + -7x Combine like terms: 6x + -7x = -1x 21 + -1x = 23 + 7x + -7x Combine like terms: 7x + -7x = 0 21 + -1x = 23 + 0 21 + -1x = 23 Add '-21' to each side of the equation. 21 + -21 + -1x = 23 + -21 Combine like terms: 21 + -21 = 0 0 + -1x = 23 + -21 -1x = 23 + -21 Combine like terms: 23 + -21 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| -3w+2=14 | | 25000x-5y=0 | | X+1.23=65.6 | | 15y-1=103 | | 9x-38=4x+23 | | 11-(x-2)=3 | | 4x+6=9x+1 | | 3x+3(5x-15)=63 | | 8+c=0 | | 8=c-12 | | x^2-14x+40=40 | | -0.23076923p=-2 | | -4(t-4)+9t=7t-6 | | (x-10)(x-4)=40 | | -3(1.2)(1.2)= | | 7y+5=9y | | 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 |